2020
DOI: 10.1038/s41467-019-13909-5
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient all-inorganic perovskite solar cells with suppressed non-radiative recombination by a Lewis base

Abstract: All-inorganic perovskite solar cells (PVSCs) have drawn increasing attention because of their outstanding thermal stability. However, their performance is still inferior than the typical organic-inorganic counterparts, especially for the devices with p-in configuration. Herein, we successfully employ a Lewis base small molecule to passivate the inorganic perovskite film, and its derived PVSCs achieved a champion efficiency of 16.1% and a certificated efficiency of 15.6% with improved photostability, representi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
359
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 451 publications
(370 citation statements)
references
References 67 publications
10
359
0
1
Order By: Relevance
“…In addition, the MABrEthPerovskite exhibits an obvious increased PL inten sity compared with EthPerovskite, implying a significant sup pressed nonradiative recombination due to MABr passivates the defects. [27] TRPL results of samples were fitted by biexpo nential decay function with PL lifetime (τ i ) and amplitudes (A 1 ), followed by the equation of in Figure S2 and corresponding parameters are summarized in Table S1 of the Supporting Information. τ 1 is closely related to nonradiative recombination by defects and τ 2 as a component of radiative recombination from perovskite.…”
Section: Doi: 101002/adma202003965mentioning
confidence: 99%
“…In addition, the MABrEthPerovskite exhibits an obvious increased PL inten sity compared with EthPerovskite, implying a significant sup pressed nonradiative recombination due to MABr passivates the defects. [27] TRPL results of samples were fitted by biexpo nential decay function with PL lifetime (τ i ) and amplitudes (A 1 ), followed by the equation of in Figure S2 and corresponding parameters are summarized in Table S1 of the Supporting Information. τ 1 is closely related to nonradiative recombination by defects and τ 2 as a component of radiative recombination from perovskite.…”
Section: Doi: 101002/adma202003965mentioning
confidence: 99%
“…Besides, some other small molecules, such as a π‐conjugated Lewis base 6TIC‐4F, which contains a strong electron‐donating core and two electron‐withdrawing units, were dissolved in the anti‐solvent to passivate the surface defects on the perovskite thin films, therefore improving the CsPbI 3 perovskite quality. [ 68 ]…”
Section: Solution Chemistry Preparation Of Cspbi3 Inorganic Perovskitementioning
confidence: 99%
“…[ 41–43 ] Recently, it was reported that a nonfullerene Lewis base could passivate inorganic perovskite (CsPbI x Br 3− x ) through interaction between Pb and CN groups/S atoms. [ 44 ] PbI 2 is rich on the surface of PQDs (positively charged), and capping reagents such as oleylamine and oleic acid can passivate the surface. [ 39,45 ] However, the capping reagents are easily removed, resulting in surface defects and degradation of PQDs.…”
Section: Figurementioning
confidence: 99%